2015
DOI: 10.1212/wnl.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin for frontotemporal dementia

Abstract: This study provides Class I evidence that for patients with FTD, intranasal oxytocin is not significantly associated with adverse events or significant changes in the overall neuropsychiatric inventory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 25 publications
(26 reference statements)
1
76
0
1
Order By: Relevance
“…Oxytocin through interactions with gonadal hormones has also been suggested to affect sexual function [45], with decreased levels or action potentially producing decreased sexual drive. When bvFTD patients are administered oxytocin a proportion develop hypersexual behavior [46]. As such, it is possible that neuroendocrine abnormalities modulate hyposexual behavior, and this proposal requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin through interactions with gonadal hormones has also been suggested to affect sexual function [45], with decreased levels or action potentially producing decreased sexual drive. When bvFTD patients are administered oxytocin a proportion develop hypersexual behavior [46]. As such, it is possible that neuroendocrine abnormalities modulate hyposexual behavior, and this proposal requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, other novel approaches to managing behavioral symptoms for FTD are currently being studied in placebocontrolled trials. The neuropeptide oxytocin, an important mediator of social behavior, was administered intranasally to 20 bvFTD and three svPPA patients in a double-blind, randomized, placebo-controlled, crossover trial over 1 week and demonstrated possible trend toward improved apathy and empathy (Finger et al 2015).…”
Section: Behavioral Symptoms Managementmentioning
confidence: 99%
“…The study by Finger and colleagues did not report significance for measures given the small sample size [Finger et al 2015]. Trends were found in improvements on the NPI, FBI, and the Interpersonal Reactivity Index (IRI) in the oxytocin group.…”
Section: Resultsmentioning
confidence: 95%
“…This systematic review of the literature only identified two RCTs that evaluated the use of oxytocin in individuals with FTD [Jesso et al 2011;Finger et al 2015]. Both studies were of good quality based on the criteria developed by the Center for Evidence Based Medicine [CEBM, 2014].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation